Monoclonal Antibodies From Anti-NMDA Receptor Encephalitis Patient as a Tool to Study Autoimmune Seizures - Taraschenko, Olga; Fox, Howard S.; Eldridge, Ember; Wang, Wenyi; Dowd, Samuel W.; Al-Saleem, Fetweh; Kattala, Chandana Devi; Dessain, Scott K.; Dingledine, Raymond (Frontiers in Neuroscience, 2021)
Anti-N-methyl-D-aspartate (NMDA) receptor encephalitis manifests with precipitous cognitive decline, abnormal movements, and severe seizures that can be challenging to control with conventional anti-seizure medications. We previously demonstrated that intracerebroventricular (i.c.v.) administration of cerebrospinal fluid from affected patients, or purified NMDA receptor antibodies from encephalitis patients to mice precipitated seizures, thereby confirming that antibodies are directly pathogenic for seizures. Although different repertoires of anti-NMDA receptor antibodies could contribute to the distinct clinical manifestations in encephalitis patients, the role of specific antibodies in the expression of seizure, motor, and cognitive phenotypes remains unclear. Using three different patient-derived monoclonal antibodies with distinct epitopes within the N-terminal domain (NTD) of the NMDA receptor, we characterized the seizure burden, motor activity and anxiety-related behavior in mice. We found that continuous administration of 5F5, 2G6 or 3C11 antibodies for 2 weeks precipitated seizures, as measured with continuous EEG using cortical screw electrodes. The seizure burden was comparable in all three antibody-treated groups. The seizures were accompanied by increased hippocampal C-C chemokine ligand 2 (CCL2) mRNA expression 3 days after antibody infusion had stopped. Antibodies did not affect the motor performance or anxiety scores in mice. These findings suggest that neuronal antibodies targeting different epitopes within the NMDA receptor may result in a similar seizure phenotype.